Government's liability on tsunami / Siti Nuramani Abd Manab, Cartaz Ummu Syawaeda Jaiman and Rahidatulakma Rasedi - Abd Manab, Siti Nuramani; Jaiman, Cartaz Ummu Syawaeda; Rasedi, Rahidatulakma (2005)
Our research is on government's liability on tsunami as it has caused the death of the people and the property damage. The objective of the research is to see whether the government has fails in formulating and implementing an adequate and effective policy on disaster management to deal with the impact of the earthquake. As we know, tsunami is the result of the occurrence of earthquake which was occurred in the sea. Prior to 26th December 2004, we do not have any policy on disaster management with regard to the earthquake although we had experienced the effect of the earthquake in late 90's in certain part of Malaysia. Thus, when our country has not being prepared at all to deal with the situation. However, after 26th December 2004 the government has actively involved in die society to ensure the effectiveness of the policy on disaster management with regard to tsunami. Among of their efforts is that by held on a series of talks, training on how people should react if there is real impending tsunami. Apart from that, with regard to the early warning system on tsunami, our country is in the process of setting up the warning system by the cooperation with other Asian Countries, Therefore, with regard to the implementation of an adequate policy on disaster management, if the government implement such policy earlier, the impact of tsunami in our country may be mitigate by relying on the experience of the earthquake in late 90's. Thus, the government should be held liable since they have fails to formulate and implement an adequate policy on disaster management with regard to tsunami.